An inhibitor of oil body mobilization in Arabidopsis. Issue 3 (27th August 2013) - Brown, Laura‐Anne; Larson, Tony R.; Graham, Ian A.; Hawes, Chris; Paudyal, Rupesh; Warriner, Stuart L.; Baker, Alison
Summary Fatty acid β‐oxidation is an essential process in many aspects of plant development, and storage oil in the form of triacylglycerol (TAG) is an important food source for humans and animals, for biofuel and for industrial feedstocks. In this study we characterize the effects of a small molecule, diphenyl methylphosphonate, on oil mobilization in Arabidopsis thaliana. Confocal laser scanning microscopy, transmission electron microscopy and quantitative lipid profiling were used to examine the effects of diphenyl methylphosphonate treatment on seedlings. Diphenyl methylphosphonate causes peroxisome clustering around oil bodies but does not affect morphology of other cellular organelles. We show that this molecule blocks the breakdown of pre‐existing oil bodies resulting in retention of TAG and accumulation of acyl CoAs. The biochemical and phenotypic effects are consistent with a block in the early part of the β‐oxidation pathway. Diphenyl methylphosphonate appears to be a fairly specific inhibitor of TAG mobilization in plants and whilst further work is required to identify the molecular target of the compound it should prove a useful tool to interrogate and manipulate these pathways in a controlled and reproducible manner.